Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017; Session "Perinatal Pharmacology and Anesthesia" - - (Hygeia Press di Corridori Marinella, 2017)
Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017 58th ESPR Annual Meeting, 7th International Congress of UENPS, 3rd International Congress of EFCNI ORGANIZING INSTITUTIONS European Society for Paediatric Research (ESPR), European Society for Neonatology (ESN), Union of European Neonatal & Perinatal Societies (UENPS), European Foundation for the Care of Newborn Infants (EFCNI) ORGANIZING COMMITTEE Luc Zimmermann (President of ESPR), Morten Breindahl (President of ESN), Manuel Sánchez Luna (President of UENPS), Silke Mader (Chairwoman of the Executive Board and Co-Founder of EFCNI) SCIENTIFIC COMMITTEE Virgilio P. Carnielli (Congress President Chair), Pierre Gressens (Past Scientific President), Umberto Simeoni, Manon Benders, Neil Marlow, Ola D. Saugstad, Petra Hüppi, Agnes van den Hoogen Session "Perinatal Pharmacology and Anesthesia" ABS 1. UNDERSTANDING THE RELATIONSHIP BETWEEN DOPAMINE CONCENTRATION AND BLOOD PRESSURE IN NEONATES: INCUBATORS VERSUS COT • K. Kirupakaran, H. Rabe, B. Patel ABS 2. IBUPROFEN PHARMACOGENETIC STUDY IN HUMAN MILK SAMPLES • V. Rigourd, C. Verstyuft, J.F. Méritet, P. Seraissol, B. De Villepin, A. Amirouche, R. Serreau ABS 3. EFFECT OF POSTNATAL CORTICOSTEROID ON BROWN ADIPOSE TISSUE THERMOGENESIS IN NEONATAL RAT • Y.-S. Chang, C.-H. Lin, Y.-S. Tsai ABS 4. URINARY 17-α-HYDROXY-PROGESTERONE AS A POTENTIAL MARKER OF NEONATAL PAIN • M. Brasseler, T. Hoehn ABS 5. PHARMACOKINETIC AND PHARMACODYNAMIC STUDIES AIMING FOR RATIONAL DRUG DOSING IN PRETERM NEONATES: THE DINO STUDY • R.B. Flint, S. Völler, R. de Groot, D. Liem, P. Andriessen, P. Degrauewe, I. Reiss, D. Burger, D. Tibboel, C.A.J. Knibbe, S.H.P. Simons and DINO Research group ABS 6. VENO-ARTERIAL EXTRACORPOREAL MEMBRANE OXYGENATION IMPAIRS ACETYLCHOLINE-INDUCED CONTRACTION IN NEONATAL PORCINE CORONARY ARTERIES • L. Provitera, G. Cavallaro, G. Raffaeli, I. Amodeo, S. Gulden, G. Zuanetti, V. Gentilino, F. Macchini, E. Villamor, F. Mosca ABS 7. β3-ADRENOCEPTOR REGULATION OF NITRIC OXIDE IN THE CORD VASCULAR SYSTEM • G. Cavallaro, A. Griggio, L. Provitera, G. Raffaeli, I. Amodeo, S. Gulden, G. Zuanetti, D. Lattuada, G. Ercoli, S. Gatti, E. Villamor, F. Mosca ABS 8. BIG DATA ANALYSES FOR CONTINUOUS EVALUATION OF PHARMACOTHERAPY: A PROOF OF PRINCIPLE WITH DOXAPRAM FOR PRETERM INFANTS • R. Flint, W. van Weteringen, S. Völler, J. Poppe, B. Koch, R. de Groot, D. Tibboel, C. Knibbe, I. Reiss, S. Simons, DINO Research group ABS 9. ADRIN 1 METHODOLOGY STUDY: ADVERSE DRUG REACTIONS IN NEONATES: WHAT ARE THE BEST WAYS TO EVALUATE SUSPECTED ADVERSE DRUG REACTIONS IN NEONATES? • E. Roberts, D. Hawcutt, J.J. Kirkham, M.A. Turner ABS 10. LARGE DIFFERENCES IN OFF-LABEL AND NEONATAL DRUG USE STILL EXIST: TIME FOR CONSENSUS? • R. Flint, F. Van Beek, P. Andriessen, P. Degraeuwe, D. Liem, I. Reiss, R. de Groot, D. Tibboel, D. Burger, S. Simons; DINO study group